Future accessibility impacts of transport policy scenarios: Equity and sensitivity to travel time thresholds for Bus Rapid Transit expansion in Rio de Janeiro. (January 2019) - Pereira, Rafael H.M.
Abstract: The accessibility impacts of transport projects ex-post implementation are generally evaluated using cumulative opportunity measures based on a single travel time threshold. Fewer studies have explored how accessibility appraisal of transport plans can be used to evaluate policy scenarios and their impacts for different social groups or examined whether the results of project appraisals are sensitive to the time threshold of choice. This paper analyzes how different scenarios of full and partial implementation of the TransBrasil BRT project in Rio de Janeiro (Brazil) will likely impact the number of jobs accessible to the population of different income levels. The analysis is conducted under various travel time thresholds of 30, 60, 90 and 120 min to test whether the results are sensitive to the boundary effect of the modifiable temporal unit problem (MTUP). Compared to a partial operation scenario, the full implementation of TransBrasil that extends this corridor into the city center would lead to higher accessibility gains due to network effects of connecting this BRT to other transport modes. Nonetheless, the size of the accessibility impacts of the proposed BRT as well as its distribution across income classes would significantly change depending on the time threshold chosen for the accessibility analysis. Considering cut-off times of 30 or 60 min, both scenarios of TransBrasil would lead to higher accessibility impacts in general and particularly for low-income groups, moving Rio towards a more equitable transportation system. However, under longer thresholds of 90 and 120 min, an evaluation of this project would find much smaller accessibility gains more evenly distributed by income levels. The paper highlights how time threshold choice in cumulative opportunity measures can have important but overlooked implications for policy evaluation and it calls for further research on the MTUP in future transport and mobility studies. Highlights: The study estimates how the TransBrasil BRT project in Rio de Janeiro will likely impact employment accessibility for different income groups The full implementation of the proposed BRT could benefit up to 58% of the city population, increasing job accessibility by 11% on average This BRT project could substantially improve accessibility for lower-income groups and reduce inequalities in access to opportunities The study shows that the conclusions of equity assessments of transport projects depend on the travel time threshold chosen for cumulative opportunity accessibility analysis